AC susceptibility, DC magnetization and superconducting properties of tungsten oxide nanowires added YBa2Cu3Oy. Issue 17 (1st December 2019) - Slimani, Y.; Almessiere, M.A.; Hannachi, E.; Al-qwairi, F.O.; Manikandan, A.; Baykal, A.; Ben Azzouz, F.
Abstract: In this report, the impact of tungsten oxide nanowires (noted WO3 -NWs) inclusion on the AC susceptibility, DC magnetization and superconducting properties of YBa2 Cu3 Oy (noted Y-123) was investigated. Non-added and WO3 -NWs added to Y-123 samples were produced using solid-state reaction route. Prepared samples were characterized by using numerous techniques, such X-rays diffraction (XRD), scanning electron microscopy (SEM) along with energy-dispersive X-ray (EDX) spectroscopy, electrical resistivity, magnetization hysteresis loops, zero-field cooling and field-cooling (ZFC-FC) magnetizations and AC susceptibility measurements. The successful development of the orthorhombic Y-123 phase was confirmed via XRD and EDX analyses. SEM observations showed that the WO3 -NWs provoke an enhancement of the connectivity among grains and reduces the porosity by entering between the grains and filling the voids among them. Measurements of electrical resistivity and ZFC-FC magnetizations verified the manifestation of superconductivity in various samples. The magnetization and intergranular critical current densities ( J cm and J c, inter ) were deduced from various magnetic measurements. Improvements of critical current densities ( J cm and J c, inter ) and flux pinning capability were found with the inclusion of NW-WO3 into Y-123 matrix.